2011
DOI: 10.1120/jacmp.v12i2.3363
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reconstruction settings on the performance of adaptive thresholding algorithms for FDG‐PET image segmentation in radiotherapy planning

Abstract: The purpose of this study was to analyze the behavior of a contouring algorithm for PET images based on adaptive thresholding depending on lesions size and target‐to‐background (TB) ratio under different conditions of image reconstruction parameters. Based on this analysis, the image reconstruction scheme able to maximize the goodness of fit of the thresholding algorithm has been selected. A phantom study employing spherical targets was designed to determine slice‐specific threshold (TS) levels which produce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Previous work has demonstrated that the choice for number of iterations and subsets do not have a marked effect on segmentations (Matheoud et al 2011) and so we feel that, together with the wide range of image acquisition parameters, our results are representative of what one would expect on different scanners/iterative reconstruction algorithms.…”
Section: Discussionsupporting
confidence: 66%
“…Previous work has demonstrated that the choice for number of iterations and subsets do not have a marked effect on segmentations (Matheoud et al 2011) and so we feel that, together with the wide range of image acquisition parameters, our results are representative of what one would expect on different scanners/iterative reconstruction algorithms.…”
Section: Discussionsupporting
confidence: 66%
“…In fixed thresholding, a clinically accepted value of SUV = 2.5 or 40% of the SUV max (i.e., maximum SUV of a predefined region) is used to delineate lesions from the background for a given region of interest (ROI) drawn manually (Nestle et al, 2006). In adaptive thresholding methods, a more optimal thresholding level is searched by examining class uncertainties (Otsu, 1979), by building realistic phantoms (Matheoud et al, 2011; Davis et al, 2006; Brambilla et al, 2008; Schaefer et al, 2008), by applying iterative thresholding based on scanner hardware properties (Drever et al, 2007; van Dalen et al, 2007; Jentzen et al, 2007), or by incorporating local approaches into the threshold selection process (Erdi et al, 2002; Bradley et al, 2004; Ciernik et al, 2005; Koshy et al, 2005). It has been shown in various studies (Fahey et al, 2010) that the lack of optimal threshold levels in these approaches prevents accurate and robust delineation of lesions from the background.…”
Section: Introductionmentioning
confidence: 99%
“…T. Schakel, et al Physics and Imaging in Radiation Oncology 5 (2018) [13][14][15][16][17][18] values. Jager et al [5] showed 0.61 for laryngeal cancer using CT and 0.57 using CT/MR; Geets et al reported 0.41 and 0.42 for laryngeal and oropharyngeal GTVs respectively [30]; Mukesh et al reported 0.54 for CTV delineations on CT [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of PET for segmentation is challenging. The segmentations can depend on the contrast and noise characteristics of the PET images, which, apart from tumor characteristics, originate from different acquisition and reconstruction protocols [15] , [16] . Additionally, a variety of segmentation algorithms have been proposed which result in large variations in target volumes [10] , [17] .…”
Section: Introductionmentioning
confidence: 99%